Protective role of zingerone against high glucose-Induced retinal pigment epithelial cell damage through modulation of the TRPM2 channel pathway (vo 53, pg 309, 2026) - Cig, Esmanur; Yardimci, Mahmut; Cinar, Ramazan; Yildizhan, Kenan (Springer, 2026)
[Keywords Not Available]
Keywords: [Keyword Not Available]